COMMUNICATIVE LANGUAGE TEACHING - Pardayev O’tkir; Sanayeva Gulsanam; Qosimov Anvar (Galaxy International Interdisciplinary Research Journal, 2023)
Communicative language teaching (CLT), or the communicative approach (CA) , is an approach to language teaching that emphasizes interaction as both the means and the ultimate goal of study.